Questioning the benefits that coloured overlays can have for reading in students with and without dyslexia - Henderson, L; Tsogka, N; Snowling, M (2013)
Visual stress (the experience of visual distortions and discomfort during prolonged reading) is frequently identified and alleviated with coloured overlays or lenses. Previous studies have associated visual stress with dyslexia and as a consequence, coloured overlays are widely distributed to children and adults with reading difficulty. However, this practice remains controversial. We investigated whether overlays have advantageous and reliable benefits for reading in undergraduate students with and without dyslexia. Both groups read jumbled text faster with a coloured overlay than without. The dyslexic group did not show greater gains than controls, despite reporting significantly more symptoms of visual stress. However, coloured overlays did not improve reading rate or comprehension of connected text. The improvement in reading speed with an overlay was not reliable and was significantly reduced at retesting for dyslexic students. These results question the value of coloured overlays as a tool for identifying visual stress and as a form of remediation for the reading difficulties associated with dyslexia. © 2012 The Authors. Journal of Research in Special Educational Needs © 2012 NASEN.